(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This research is an attempt to investigate the micropaleontology of the Yolde Formation with the view to determine the age and paleoenvironments of the formation. The Yolde Formation, a key stratigraphic unit within the Benue Trough, provides insights into the Cretaceous paleoenvironments of the region. A total of ten samples were examined using a light microscope. Samples two and six exhibited the greatest taxonomic diversity, each containing 13 different taxa, while the other samples showed a range of 1 to 11 taxa. The benthic taxa Marssonella, Ammobaculites agulutinans, and Plectina were found to be prevalent throughout the composite section. Certain taxa, such as Marssonella Verneuilinoides Sp., Gyroidinoides sp., and Textularia subhauriiw, each constituted approximately 30% of the benthic assemblage. Common benthic indicators identified in the Yolde Formation include Marssonella, Verneuilinoides Sp., Ammobaculites agulutinans, Plectina cenomana Sp., Tritaxia tricarinata, Gyroidinoides Sp., Heterohelix Sp. etc. The presence of Bulbobaculite Sp. and Gavelinella Sp. in the Yolde Formation indicates that this formation dates to the Cenomanian age. This dating is supported by the identification of other foraminifera such as Marssonella, Verneuilinoides sp., Ammobaculites agulutinans, Plectina cenomana sp., Tritaxia tricarinata, Gyroidinoides sp., Heterohelix sp., etc. These benthic foraminifera are linked to low-oxygen paleoenvironments that reached the seabed. The presence of Ammobaculites Spp., Tritaxia tricarinata, and Gyroidinoides Sp. suggests anoxic conditions. Consequently, the paleoenvironments represented by the benthic foraminifera and the lithofacies reflects a paleoenvironments ranging from inner neritic to middle neritic zones within lower shoreface to upper shoreface.